Perceived and observed translational norms in biomedical translation in the contemporary Portuguese translation market : a quantitative and qualitative product- and process-oriented study - Valdez, Susana Santos Ângelo Salgado (2019)
At the intersection of Descriptive Translation Studies and Social Sciences, this interdisciplinary, empirical, experimental and descriptive study addresses the question of ascertaining whether and to what extent translators’ decision-making processes are influenced by what translators believe to be the expectations of other agents, namely revisers and readers. Whereas preferences by translators have previously been described and explained in the literature, it is still unclear what revisers’ and readers’ translational preferences are and what expectations they have about translators and the translated text. In addition, there is still a lack of understanding about how translators translate, how translators think they should translate, and what translators believe to be the expectations of other translators, revisers, and readers. In order to address these issues, this study focuses on the distinction between observed and perceived norms in the translation of biomedical texts from English to European Portuguese in contemporary Portugal. It zooms in on preferences regarding source and target orientation in translation, comparing both the practice and beliefs of sixty agents with different roles and levels of experience: novice translators, experienced translators, revisers, and health professionals (representing the intended audience of the target text). In particular, the specific question which drives this research is: considering English to European Portuguese biomedical translation in the contemporary Portuguese market, are the observed translational norms and perceived translational norms of translators, revisers and readers similar or different regarding source and target orientation? Mainly informed by the metatheoretical, theoretical, and methodological discussions of Toury (1995, 2012), Hermans (1991; 1996; 1999a; 1999b; 2000), Bicchieri (2006, 2017a, and 2017b), and Rosa (2016c), norms and expectations emerge as a powerful descriptive tool in studying norm-governed behavior and specifically to capture and further understand the complexities of decision-making processes in translation. Based on an exploratory and preliminary case study, this dissertation first sets out to explore the practice of biomedical translation in Portugal to understand who the agents involved in biomedical translation are, what they do, what for, in what types of texts, with what function and for whom. To this end, a mixed corpus of 700,000 words of different text-types of medical and biomedical content translated from English to European Portuguese was analyzed, including e-mail exchanges between translators and project managers. This analysis shows that biomedical translation involves a complex structure of translation agents performing different translation tasks, among which revisers play a pivotal role. The most common text-type identified is instructional texts about medical devices aimed at health professionals. Following this preliminary assessment, for the main study, a mixed methodology based on quantitative and qualitative product- and process-oriented approaches was employed to study (i) thirty translations of an instructional text about a medical device intended for health professionals, (ii) the translational preferences of fifteen revisers and fifteen health professionals regarding the same instructional text, and (iii) the expectations of these translators, revisers, and health professionals about biomedical translation. The experiment involved eliciting data from fifteen novice translators and fifteen experienced translators asked to translate an instructional text. The data included keylogging and screen recording data, interim versions and target texts, and it was triangulated to produce an empirical description of translation phenomena of biomedical content. The data was analyzed in terms of (i) the translators’ translation problems, (ii) the corresponding observed translation solutions, and (iii) the source and target orientation of the solution types. In addition, the thirty translators, together with fifteen specialized revisers and fifteen health professionals, were asked to answer a questionnaire aimed at eliciting different types of beliefs and expectations to (i) analyze the translators’ expectations and perceptions about how they should translate and how other translators, revisers, and readers believe translators should translate, (ii) identify the revisers’ and health professionals’ translational preferences, and (iii) describe an elaborate network of beliefs and expectations affecting the translators’ decision-making processes that result from the interaction of several agents with different roles and levels of normative control, and (iv) to propose explanatory hypotheses for the identified translation phenomena. From the product analysis, the study found that (i) the novice and experienced translators opted for both source- and target-oriented translation solutions, while (ii) the revisers and health professionals opted for the most target-oriented translations. The most common target-oriented translation solutions (i.e., explicitation, implicitation, hyponymy/hypernymy, omission, addition, and other information changes) were also analyzed in terms of their textual function and potential motivations to propose explanatory hypotheses. From the process analysis, the comparison of the translators’ interim versions and final versions indicated that while (i) the novice translators proceeded from less source-oriented versions to more source-oriented ones, (ii) the experienced translators proceeded from more source-oriented versions to less source-oriented ones. From the analysis of the beliefs and expectations, the study found that (i) while the novice and experienced translators described the appropriateness of a translation using both source- and target-oriented criteria, (ii) the revisers and health professionals reported target-oriented criteria as the most important to describe the appropriateness of a translation. Overall, the novice and experienced translators’ behavior and expectations suggested initial norms of source and target orientation, revealing that aspects of both the source and target cultures and languages are valued. The analysis of the processes of the novice and experienced translators also suggested that there are other possible motivations for source and target orientation connected with (i) the number of translation problems and (ii) the time taken to translate the source text. Revisers’ and health professionals’ behavior and expectations suggested an initial norm of target orientation, revealing a higher valuation of the target culture, language, and prospective reader. The study also found that even though accuracy (a source-oriented criterion) is a common expectation among all agents, expectations regarding literal translation (source-oriented), transparency, and invisibility (target-oriented) are not shared by translators, revisers, and health professionals. By showing how perceptions and expectations about source and target orientation may influence translators’ textual regularities, the findings of this descriptive, target-oriented study add to our understanding of translational norms in general and in biomedical translation in particular. The main implications of this study are of four different types: theoretical, methodological, practical and didactic. This study raises theoretical implications that have a bearing on translational norms. In particular, it proposes a definition of translational norms that (i) allows for a distinction between object- and meta-level discourses (building on Rosa 2016c), (ii) explicitly includes the role of agents’ expectations as a driver of behavior, connoting what is considered appropriate and inappropriate (adapted from Bicchieri 2017a), and (iii) stresses the need to address different and sometimes conflicting perceptions of what is considered appropriate and inappropriate in a particular community. In addition, the study also offers methodological tools to address norms by proposing that translational norms can be further studied through the comparative analysis of a detailed taxonomy of beliefs, attitudes, and expectations elicited from different agents with various roles (adapted from Bicchieri 2017a). It also describes how translation problems can be identified based on keylogging and screen recording data through a fine-grained classification of translation units based on primary and secondary indicators of translation problems (building on Krings 1986; and Göpferich 2010b) in order to reconstruct the decision-making processes of the translator and, in particular, the methodological distinction between an interim solution and a consciously postponed decision. The described regularities and expectations expressed by the data also have implications for translation practice and translator training. The findings can be used to develop concrete solutions to address translation competence and best practices for the language industry. It is recommended that students should be specifically trained to raise self-awareness to monitor and assess, in their translation and revision decision-making processes, how their expectations about translation and their perceived expectations about revisers and readers can be related to their translation solutions. Given that communication between professional translators and revisers can be a factor for the distinct perceptions identified regarding expectations, best practices for peer feedback are also proposed. In addition, universities are called to action to promote communication among professional translators, revisers and readers in specialized domains, addressing at the same time the gap between academic work and the language industry.